Academic Senate Minutes 2002-10-03 - Academic Senate:::::::::
Report from Chair. Agenda amended and approved. Minutes amended and approved. Update on Provost Search Committee. School Calendar for 2005/2006 and 2006/2007 approved. First Reading of Resolution: Audit of Greenhouse Gas Emissions. First Reading Constitutional Amendment regarding Article III, Section 2.2. Constitutional Amendment and By-Laws Change regarding Staff Requirements received short discussion. Resolution on Search for Provost approved.